We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
128
1
avatar

Let the roots of \(z^3 = 2 + 2i\) be \(a_1 + ib_1, a_2 + ib_2,\) and \(a_3 + ib_3.\) Compute \(a_1 a_2 a_3.\)

 Apr 16, 2019
 #1
avatar+23071 
+2

Let the roots of

\(z^3 = 2 + 2i \)

be \(a_1 + ib_1\)\(a_2 + ib_2\) and \(a_3 + ib_3\).
Compute \(a_1 a_2 a_3\).

 

\(\begin{array}{|rcll|} \hline \mathbf{z^3} &\mathbf{=}& \mathbf{2 + 2i},\ \quad z^3=a+ib \\\\ && \text{convert 2+2i to polar form:}\\ && r = \sqrt{a^2+b^2} = \sqrt{2^2+2^2} = \sqrt{8}= \sqrt{2^3} \\ && \sqrt[3]{r} = \sqrt[3]{\sqrt{2^3} } = \sqrt[3]{ 2^\frac{3}{2} } = \left( 2^\frac{3}{2} \right)^{\frac{1}{3} } = 2^\frac{1}{2} = \sqrt{2} \\ && \theta = \arctan\left(\dfrac{b}{a}\right) = \arctan\left(\dfrac{2}{2}\right) = \dfrac{\pi}{4} \\ && \theta_i = \dfrac{\dfrac{\pi}{4}+2\pi k} {3} \\ && \theta_i = \dfrac{\pi}{12} + \dfrac{2}{3} \pi k ,\quad k= 0,\ 1, 2 \\\\ && \theta_1 = \dfrac{1}{12} \pi,\quad \theta_2 = \dfrac{3}{4} \pi, \quad \theta_3 = \dfrac{17}{12} \pi \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline z_0 &=& \sqrt{2} \left( \cos\left( \dfrac{1}{12} \pi\right) +i\sin\left(\dfrac{1}{12} \pi \right)\right) \quad | \quad \cos\left( \dfrac{1}{12} \pi\right) = \dfrac{\sqrt{2}(\sqrt{3}+1) }{4} \\ z_1 &=& \sqrt{2} \left( \cos\left( \dfrac{3}{4} \pi\right) +i\sin\left(\dfrac{3}{4} \pi \right)\right) \quad | \quad \cos\left( \dfrac{3}{4} \pi\right) = -\dfrac{\sqrt{2}}{2} \\ z_2 &=& \sqrt{2} \left( \cos\left( \dfrac{17}{12} \pi\right) +i\sin\left(\dfrac{17}{12} \pi \right)\right) \quad | \quad \cos\left( \dfrac{17}{12} \pi\right) = -\dfrac{\sqrt{2}(\sqrt{3}-1) }{4} \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline \mathbf{a_1 a_2 a_3} &=& \sqrt{2} \dfrac{\sqrt{2}(\sqrt{3}+1) }{4} \sqrt{2}\left(-\dfrac{\sqrt{2}}{2}\right) \sqrt{2}\left(-\dfrac{ \sqrt{2}(\sqrt{3}-1) }{4} \right) \\ &=& \dfrac{1}{4} (\sqrt{3}+1)(\sqrt{3}-1) \\\\ &=& \dfrac{3-1}{4} \\\\ &=& \dfrac{2}{4} \\\\ &\mathbf{=}& \mathbf{\dfrac{1}{2}} \\ \hline \end{array} \)

 

laugh

 Apr 17, 2019
edited by heureka  Apr 17, 2019

26 Online Users

avatar
avatar
avatar
avatar